Empowerment of Adolescent Cadres Through Health Training and Hemoglobin Testing for Stunting Prevention - Arif Tirtana; Desto Arisandi; Fatya Nurul Hanifa (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
This activity aims to prevent stunting from an early age through the empowerment of adolescents as health cadres and early detection of hemoglobin (Hb) status in women of childbearing age. The method used is the Capacity Development approach which is carried out in the form of counseling, training in vital signs examination skills, and Hb level checks. The results showed that the training was attended by 17 teenagers from representatives of each Region in the hamlet. Meanwhile, Hb examination was carried out on 72 women of childbearing age, with results showing that 63% of respondents had normal Hb levels. This program has a positive impact on increasing adolescents' awareness and knowledge related to basic health and preparedness of women of childbearing age in dealing with pregnancy. The main benefit felt by the assisted subjects is the increase in the capacity of individuals as agents of change in society in an effort to prevent stunting sustainably.